Ethylene Glycol/Ethanol Anolyte for High Capacity Alkaline Aluminum-Air Battery With Dual-Electrolyte Configuration - Phusittananan, Tanawat; Kao-Ian, Wathanyu; Nguyen, Mai Thanh; Yonezawa, Tetsu; Pornprasertsuk, Rojana; Mohamad, Ahmad Azmin; Kheawhom, Soorathep (Frontiers in Energy Research, 2020)
Aluminum-air batteries (AABs), due to their low cost and high specific capacity, receive much attention nowadays. Nonetheless, a vital problem curbing wide application of AABs is corrosion of the aluminum (Al) anode, which is triggered by hydrogen evolution reaction (HER). Therefore, this work tackles the problem of anode corrosion in an alkaline Al-air flow battery (AAFB) by implementing a dual-electrolyte system. The battery configuration consists of an Al anode | anolyte | anion exchange membrane | catholyte | air cathode. The anolytes in this work are ethylene glycol/ethanol solutions (0, 5, 10, 20 and 30) % v/v containing 3 M potassium hydroxide (KOH). A polymer gel electrolyte (Carbopol® 940) is employed as the catholyte. The corrosion of an Al electrode in the anolytes is duly examined. It is significant that when the ratio of ethylene glycol exceeds 5 % v/v, this negatively affects the dissolution process and suppresses Al corrosion. Furthermore, the battery using the anolyte with 5% v/v ethylene glycol, at a discharge current density of 5 mA/cm2, demonstrates peak power of 3.75 mW/cm2. The battery also exhibits the highest specific discharge capacity of 2,100 mAh/gAl (70% utilization of Al) at a discharge current density of 2.5 mA/cm2. In general, the dual-electrolyte system affirms its effectiveness in controlling anodic corrosion, quelling passivation of the Al surface in the alkaline AABs and boosting discharge capacity. KOH in ethylene glycol/ ethanol solution is a promising anolyte being more environmentally friendly, less toxic and providing favorable electrochemical performance.